2013
DOI: 10.2478/bpasts-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Self-repairing of polymer-cement concrete

Abstract: Abstract. Self-repairing means ability to the total or partial recovering of the properties which were worsened as a consequence of damage of the material. The subject of the paper is evaluation of ability to self-repair of a cement composite modified with epoxy resin without a hardener. The methodology of investigation of self-repairing building materials, developed by the authors, has been described, with controllable enforcing of the limited weakening of the material. Also, the self-repair degree has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The author stated that, the properties of epoxy cement mortars without hardener improved fairly when compared to epoxy mortar with hardener. This is due to the cross-linking of an epoxy resin in the environment of Portland cement that have accessibility to react with calcium hydroxide without the presence of hardener [5].…”
Section: Introductionmentioning
confidence: 99%
“…The author stated that, the properties of epoxy cement mortars without hardener improved fairly when compared to epoxy mortar with hardener. This is due to the cross-linking of an epoxy resin in the environment of Portland cement that have accessibility to react with calcium hydroxide without the presence of hardener [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ohama and his co-workers have first proposed and demonstrated that this process can proceed inside the cement paste [22], allowing for some specific features of epoxy-cement composites, like ability to partial self-repairing [23].…”
Section: Epoxy-cement Mortars With and Without Hardenermentioning
confidence: 99%
“…Therefore, the materials of increased resistance to biocorossion and material and technological solutions facilitating repairs of damaged structures are being sought. Such repair materials may be composites with a cement-polymer matrix [14]. It is important to answer to the question: whether and to which extent these materials are susceptible to microorganism growth and what is the destruction mechanism of the latter?…”
Section: Introductionmentioning
confidence: 99%